PELATIHAN PENGGUNAAN APLIKASI E-MARKETING DENGAN KONSEP CUSTOMER RELATIONSHIP MANAGEMENT (CRM) CV. AKU TEKNOLOGI - Hetty Meileni; Yulia Hapsari; Ferizka Tiara Devani; Risky Firdaus; Arya Thomas; Rafika Ayu (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
E-Marketing is a strategy applied by companies to promote products through the internet or online platforms. The implementation of Customer Relationship Management (CRM) aims to help companies improve customer satisfaction and loyalty by enhancing customer experiences, expanding market reach, and increasing profitability. Amid rapid business growth, CRM has become an essential solution. This system enables companies to manage customer information efficiently, record all interactions, and provide more responsive services. As a result, companies can make better decisions and develop more targeted marketing strategies. This community service activity aims to provide training and guidance on using CRM-based E-Marketing applications for CV. Aku Teknologi. The outcome of this activity is an improvement in the knowledge and skills of CV. Aku Teknologi employees in South Sumatra in conducting sales and transactions of IT Security System equipment.